International journal of e-collaboration official journal of the Information Resources Management Association. - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2005)
The International Journal of e-Collaboration (IJeC) addresses the design and implementation of e-collaboration technologies, assesses its behavioral impact on individuals and groups, and presents theoretical considerations on links between the use of e-collaboration technologies and behavioral patterns. An innovative collection of the latest research findings, this journal covers significant topics such as Web-based chat tools, Web-based asynchronous conferencing tools, e-mail, listservs, collaborative writing tools, group decision support systems, teleconferencing suites, workflow automation systems, and document management technologies.
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, issue 1 (2005); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 6, issue 4 (2010).
Keywords: Reengineering (management) -- Periodicals; Virtual work teams -- Periodicals; Organizational learning -- Periodicals; Research methods; Collaborative writing tools; E-collaboration technologies in organizations; Asynchronous learning networks (ALNs); Intelligent e-collaboration technologies in organizational settings; E-business solutions; Knowledge management and organizational learning; Distributed process reengineering and process improvement; Quality certification programs; Virtual teams and virtual organizations; E-mail; Listservs; Web-based asynchronous conferencing tools; Web-based chat tools; Electronic books